Photocatalytic C-S Bond Formation Using N-Thio and N-Perthio Phthalimide Derivatives - Huang, Hsin-Ju (Université d'Ottawa / University of Ottawa, 2024)
A method for unsymmetric disulfide synthesis from carboxylic acids under photoredox conditions has been developed. N-Perthiophthalimide derivatives (Harpp reagents) are used as disulfurating reagents in a decarboxylative disulfuration. Though significant sulfide formation was observed when using less sterically-hindered (primary and secondary) Harpp reagents, tertiary Harpp reagents affording corresponding disulfides in good yields. At first glance, the reaction was expected to go through radical substitution directly on the Harpp reagent to obtain the observed disulfide and a phthalimidyl radical that would reoxidize the reduced photocatalyst. However, computational studies suggest a high barrier and endergonic reaction for such a mechanism due to the high energy of the liberated phthalimidyl radical (N-H BDE in phthalimide is predicted to be ~120 kcal/mol). Supported by calculation and experiments, an alternative mechanism was proposed: perthyl radicals generated from single electron reduction of Harpp reagent dimerized to form tetrasulfides, which are known to undergo efficient radical substitution to afford disulfides. Mechanistic studies on previously reported sulfurations using N-thiophthalimide derivatives suggested a similar mechanism - specifically that disulfides generated in situ undergo radical substitution to provide the sulfide products. Direct C-H disulfuration using Harpp reagents under a variety of conditions was also investigated, but found to have very limited substrate scope. It would appear that the instability of the disulfurating reagents, be they Harpp reagents or tetrasulfides generated therefrom, under the various oxidative conditions prevented the development of a general approach.
Keywords: disulfuration; phthalimide reagent